Activation for Poverty Reduction : Realizing the Potential of Armenia’s Social Safety Nets - Morgandi, Matteo; Posadas, Josefina; Damerau, Tomas (World Bank, Washington, DC, 2015)
Since the peak of the economic crisis, poverty reduction in Armenia has made limited progress, with poverty rates moving from 34.1 percent in 2009 to 32 percent in 2013. This slow pace has been mirrored by the limited progress of the labor market (LM), particularly in terms of job-creation. In 2013, about 36 percent of people worked in the agricultural sector, and about half of all workers earned wages through informal jobs. These conditions highlight the need to have a robust social protection (SP) system that not only offers adequate protection to people living in poverty but can also serve as a tool to increase the quality of human capital, which in turn can help improve their economic opportunities. The government of Armenia (GoA) has shown a clear interest in building its infrastructure to deliver SP services through integrated social service centers as a means to better harness its investment in SP. Its vision is to ultimately implement an integrated social policy that personalizes interventions and tries to address multiple constraints that people face when trying to escape poverty— not only through the provision of cash benefits. The objective of this policy note is twofold. First, it provides a diagnostic of the SP system in order to identify the key issues that could be addressed to enhance its effectiveness and efficiency to achieve greater poverty reduction. Second, the note outlines a set of options—policies and reforms—for the GoA to consider as it continues to strengthen its poverty-reduction strategy. It is important to note that the focus of the report is on social assistance (SA) and LM policies for vulnerable groups. Other key aspects of SP—such as pensions, labor regulations, or the functioning of the LM as a whole—are not addressed in this report, and they have been the subject of extensive analysis elsewhere.